AI-Enhanced Diagnostic System for Reasonable Evaluation Breast Cancer - Farheen Siddiqui,; Sarvesh Kumar,; Dr. Yusuf Perwej,; Ankit Shukla,; Dr. Nikhat Akhtar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Early identification of breast cancer is crucial for improving treatment results, and recent improvements in artificial intelligence (AI) with image processing methods have shown significant promise in raising diagnostic accuracy. This research examines the impact of several image processing techniques and artificial intelligence models on the efficacy of early breast cancer diagnosis systems. Cancer is one of the most perilous diseases for individuals, although no long-term remedy presently exists. Breast cancer is the leading cause of cancer-related death. Detecting cancer in its first stages is crucial. Although rates are increasing globally, they are higher among women in more developed regions. Although it remains in its first phases, the cancer is still curable. The prognosis and recovery of breast cancer patients are improved by early detection and prompt, effective treatment. The identification of tumors presents a considerable risk of ambiguity and erroneous detection that must be resolved. Proper categorization of patients helps prevents unneeded therapies. This study's originality is found in the thorough assessment of these algorithms across several medical imaging datasets, including a UCI dataset for breast tumor picture segmentation and classification. Medical imaging research currently mostly depends on Artificial Intelligence. Machine learning-based data categorization algorithms are effective. Especially in the field of medicine, where these approaches are often used for diagnostic and analytical decision-making. Utilizing the provided data attributes, we use several machine learning approaches to ascertain if a tumor is benign or malignant in this context. This article presents a system capable of identifying breast cancer and discusses how Artificial Intelligence algorithms may improve early detection and diagnosis of the disease.
Keywords: Artificial Intelligence; Breast Cancer; Data Exploration; Classification; Convolutional Neural Network (CNN); UCI Machine Learning Repository